The Effect of Perceived Fathers Involvement on Subjective Well-being: Study On Early Adolescent Groups Who Live Without Mother In Karawang - Risma Alifa; Eko Handayani (Faculty of Psychology, Diponegoro University, 2021)
Adolescence will be even more difficult when they experience a crisis phase due to the loss of a parent, such as amother who dies, divorces, or mother as a migrant worker. This condition often occurs in Karawang and makesteenagers forced to live with their fathers who are usually perceived as less involved in their lives. In fact, thefather’s involvement is very important for adolescent’s subjective well-being, so that they can rise from thesenegative experiences. The purpose of this study was to examine the effect of perceived father’s involvement onthe subjective well-being of adolescents who live only with their father. Research respondents obtained usingconvenience sampling technique as many as 56 early adolescents (12-15 years). The researcher used aquestionnaire that containing the measuring tools of The Satisfaction with Life Scale, Positive and Negative AffectSchedule, Nurturant Fathering Scale and The Father Involvement Scale; and multiple regression for data analysis.The results showed that adolescent’s life satisfaction was influenced by father nurturance, t(53) = 2.095, p < .05,adolescent’s positive affect was partially influenced by father nurturance, t(53) = 3.088 p < .05, as well assimultaneously with father involvement, F(2, 53) = 6.657, p < .05, R2 = .201, and adolescent’s negative affect wassimultaneously influenced by father nurturance and father involvement. Thus, we hope that fathers can increasetheir role as single parents because the greater father’s involvement can affect adolescent’s higher life satisfaction,the higher positive affect and the lower negative affect, making it easier for adolescents to face the crisis phase